Perbandingan Algoritma Elias Omega Code Dan Elias Delta Code Dalam Mengkompresi File Video (Mp4) - Soraya Ainun Fitrya (Graha Mitra Edukasi, 2023)
The video file size is quite large where the better the video file quality and the longer the video file time, the file size is quite large in storing the file. With the video file size which greatly affects the length of time the video file is sent. The solution to this problem is to compress the video file. There are many algorithms in video file compression, for example the elias omega code algorithm, elias delta code, stout code, punctured elias code and many other compression algorithms. So with so many algorithms, it is necessary to test several compression algorithms or algorithm comparisons. Algorithm comparison aims to find out which algorithm is more accurate in carrying out the data compression process. The algorithms that will be compared are elias omega code and elias delta code. While the comparison parameters of the two algorithms are the compression ratio and space saving.